2018
DOI: 10.1136/bmjopen-2017-021241
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the incidence and burden of herpes zoster in New Zealand general practice: a retrospective cohort study using a natural language processing software inference algorithm

Abstract: ObjectiveTo investigate the incidence of primary care presentations for herpes zoster (zoster) in a representative New Zealand population and to evaluate the utilisation of primary healthcare services following zoster diagnosis.DesignA cross-sectional retrospective cohort study used a natural language processing software inference algorithm to identify general practice consultations for zoster by interrogating 22 million electronic medical record (EMR) transactions routinely recorded from January 2005 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“… 54 Except for one Japanese study that did not report the incidence for persons ≥75 YOA 45 and one Chinese study, 66 all Asian studies reported a drop in incidence for the highest age groups. 47 , 48 , 59 , 61 , 62 , 67 , 82 Furthermore, 2 Italian studies, 69 , 71 2 Spanish studies, 56 , 57 one UK study 37 and one study from New Zealand 75 reported a decline in the incidence for the highest age groups. From the other European countries, Australia, Canada and the USA, no studies were found that solely reported a declining incidence in the highest age groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 54 Except for one Japanese study that did not report the incidence for persons ≥75 YOA 45 and one Chinese study, 66 all Asian studies reported a drop in incidence for the highest age groups. 47 , 48 , 59 , 61 , 62 , 67 , 82 Furthermore, 2 Italian studies, 69 , 71 2 Spanish studies, 56 , 57 one UK study 37 and one study from New Zealand 75 reported a decline in the incidence for the highest age groups. From the other European countries, Australia, Canada and the USA, no studies were found that solely reported a declining incidence in the highest age groups.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 69 individual studies are provided in Table 1 . The majority of studies were conducted in the United States of America (USA; n = 14), 6 , 15–27 followed by Canada (n = 6), 28–33 the United Kingdom (UK; n = 6), 34–39 Germany (n = 5), 40–44 Japan (n = 5), 45–49 the Netherlands (n = 5), 36 , 50–53 Spain (n=5), 54–58 Taiwan (n = 4), 59–62 Australia (n = 3), 63–65 China (n = 3), 66–68 Italy (n = 3), 69–71 France (n = 2), 72 , 73 New Zealand(n = 2), 74 , 75 Sweden (n = 2), 76 , 77 Denmark (n = 1), 78 Israel (n = 1), 79 Norway (n = 1), 80 Poland (n = 1), 81 and South Korea (n = 1). 82 One study presented data for both the Netherlands and the UK separately; 36 this study is captured within the individual countries Figure 2 ; Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is conflicting evidence regarding SES (i.e. income, deprivation) and HZ incidence, with some reporting no association, some reporting an increased risk in more deprived individuals and others reporting an inverse association [2,[37][38][39]. In…”
Section: Socio-economic Factorsmentioning
confidence: 99%
“…1,2 Constitui-se como doença infecciosa comum, dado que em média um terço da população já apresentou o quadro, sendo a incidência maior em faixas etárias avançadas, visto que há um declínio na imunidade celular com o passar do tempo. 3 A doença pode evoluir para a cura em poucas semanas ou a dor pode continuar por meses ou anos. 4,5 A persistência da dor após a cura da erupção é a complicação mais frequente, sendo denominada de neuralgia pós-herpética (NPH).…”
Section: Introductionunclassified